THE ROLE OF ATTITUDES AND INTENTIONS IN SHARIA FINANCIAL BEHAVIOR OF MSMES: A THEORY OF PLANNED BEHAVIOR APPROACH - Abdul Hafiz; Suaryansyah, Berandi; Sari, Willa Fatika; Fauzi, Ahmad; Azelya, Iis (MANAJEMEN DEWANTARA, 2025)
The objective of this research is to examine how attitudes and intentions influence the sharia-compliant financial behavior of MSME practitioners, employing the Theory of Planned Behavior (TPB) as a theoretical framework. TPB explains that actual behavior is influenced by intention, which is formed by attitudes and control of perceptual behavior. The research adopts a quantitative explanatory approach and applies the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method for data analysis. The sample consisted of 35 micro, small, and medium enterprise (MSME) actors located in Toboali District, South Bangka, selected via purposive sampling. Data were collected through a structured questionnaire based on a five-point Likert scale, measuring four main constructs: attitude (ATT), perceived behavioral control (PBC), intention (INT), and actual behavior (BEH). The results of the study show that attitude has a significant effect on actual intentions and behaviors. Intention also plays a key role as a key predictor of actual behavior, strengthening the SDG framework. However, perceptual behavior control did not show a significant effect on intentions or behavior. These findings affirm the importance of forming a positive attitude and strengthening intentions in encouraging the adoption of Islamic finance practices among MSMEs. Strategic interventions need to be directed at increasing literacy, understanding sharia values, and strengthening the internal motivation of business actors so that Islamic financial transformation can run sustainably and equivocally.